Simply providential: a Thomistic response to Schmid’s providential collapse argument against classical theism - Shields, Daniel (International journal for philosophy of religion, 2024)
Classical theism is often said to suffer from the problem of modal collapse: if God is necessary and simple then all of his effects (creatures) are also necessary. Many classical theists have turned to extrinsic predication in response: God’s simple and necessary act is compatible with any number of possible effects or no effects, and is only said to be an act of creating in virtue of the existence of the universe itself. Leftow and Schmid criticize this solution for leading to “providential collapse”: God would not have control over which creation obtains if all his intrinsic features are compatible with any possible universe. Thomistic classical theism avoids both modal collapse and providential collapse by utilizing the metaphysics of relations. With no differences within his simple essence/act, God can relate himself differently to his possible effects, willing some and not willing others. These relations determine whether or not the effects will exist. Thomistic classical theism’s version of divine simplicity is not incompatible with God having a multiplicity of relations, for the three divine persons are distinct relations within God. Divine simplicity is only incompatible with a multiplicity of absolute items within God. Furthermore, not all differences of relation are grounded in the different absolute characteristics of their relata. Rather, sometimes differences of relation themselves ground differences in the absolute characteristics of their relata. God’s divine act is thus said to be an act of willing this creation rather than that in virtue of his chosen, contingent relation to possible creatures, rather than in virtue of the creatures themselves.